Natural or artificial? Habitat-use by the bull shark, Carcharhinus leucas. - Jonathan M Werry (Public Library of Science (PLoS), 2012)
Background Despite accelerated global population declines due to targeted and illegal fishing pressure for many top-level shark species, the impacts of coastal habitat modification have been largely overlooked. We present the first direct comparison of the use of natural versus artificial habitats for the bull shark, Carcharhinus leucas, an IUCN 'Near-threatened' species--one of the few truly euryhaline sharks that utilises natural rivers and estuaries as nursery grounds before migrating offshore as adults. Understanding the value of alternate artificial coastal habitats to the lifecycle of the bull shark is crucial for determining the impact of coastal development on this threatened but potentially dangerous species. Methodology/findings We used longline surveys and long-term passive acoustic tracking of neonate and juvenile bull sharks to determine the ontogenetic value of natural and artificial habitats to bull sharks associated with the Nerang River and adjoining canals on the Gold Coast, Australia. Long-term movements of tagged sharks suggested a preference for the natural river over artificial habitat (canals). Neonates and juveniles spent the majority of their time in the upper tidal reaches of the Nerang River and undertook excursions into adjoining canals. Larger bull sharks ranged further and frequented the canals closer to the river mouth. Conclusions/significance Our work suggests with increased destruction of natural habitats, artificial coastal habitat may become increasingly important to large juvenile bull sharks with associated risk of attack on humans. In this system, neonate and juvenile bull sharks utilised the natural and artificial habitats, but the latter was not the preferred habitat of neonates. The upper reaches of tidal rivers, often under significant modification pressure, serve as nursery sites for neonates. Analogous studies are needed in similar systems elsewhere to assess the spatial and temporal generality of this research.